Pengembangan Clinical Pathway Stroke Hemoragik Berbasis 3S (SDKI, SLKI, SIKI) (Journal of Telenursing (JOTING), 2023)
This study aims to develop a clinical pathway for hemorrhagic stroke patients based on the 3S (SDKI, SLKI, SIKI). The method used is Research and Development with stages including literature study, observation evaluation, validity and reliability testing, and Focus Group Discussion (FGD). The research results show that developing a 3S-based hemorrhagic stroke clinical pathway is by clinical practice guidelines and service quality. The results of Pearson's product-moment correlation test are